Oil pollution in the Eastern Arabian Sea from invisible sources: A multi-technique approach. (September 2019) - Suneel, V.; Rao, V. Trinadha; Suresh, Gopika; Chaudhary, Aditya; Vethamony, P.; Ratheesh, R.
Abstract: The Eastern Arabian Sea (EAS) is affected by oil pollution, as often evidenced by the presence of tarballs along the West Coast of India (WCI). Tarball samples collected during May 2017 along the Goa coast were subject to biomarker fingerprints, and the results matched with Bombay High (BH) oil fingerprints. The present study primarily aims at identifying the potential minor spill areas using Sentinel-imagery. Interestingly, repeated occurrence of oil spills detected at two locations, perfectly matched with BH platforms. The simulated Lagrangian trajectories also depict that tarball particles have originated from those detected locations. In 2017 alone, the quantity of spilled oil was estimated to be 129, 392 l. However, spills detected offshore regions of Kachchh and Mangalore were found to be caused by ships. This is the first comprehensive study, tracking the oil pollution sources in the EAS through multi-technique approach - chemical, remote sensing and numerical modeling. Graphical abstract: Unlabelled Image Highlights: Hopane fingerprints identified the source of tarballs as BH oil. Repeat occurrence of spills detected at 2 locations matches the BH field platforms. Backward Lagrangian trajectory matches with the remote sensing and fingerprint data. The spills detected off Gujarat and Karnataka are caused by the ships. ≈129, 390 l of oil was spilled in the vicinity of oil fields only in 2017.